1990
DOI: 10.1007/bf01014590
|View full text |Cite
|
Sign up to set email alerts
|

Lottery play and problem gambling

Abstract: This study sought to determine if lottery play along with other possible causes engenders problem gambling. Problem gambling was defined as a progression and measured by three scales: Gambling behavior, loss of control over gambling and gambling consequences. Possible causes of problem gambling included lottery play, personality traits, exposure to gambling, leisure pursuits, marital status, residence, and other background characteristics of respondents. Respondents are a stratified random sample of adult resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Nine percent of these young people were classified by the authors as problem gamblers. Hraba, Mok, and Huff's (1990) stratified random telephone sample of 2000 Iowa residents suggested that while gambling behaviour was relatively common, the relationship of such behaviour to perceived loss of control or the experience of negative consequences was quite moderate, indicating that gambling need not be associated with undesirable outcomes or feelings.…”
mentioning
confidence: 99%
“…Nine percent of these young people were classified by the authors as problem gamblers. Hraba, Mok, and Huff's (1990) stratified random telephone sample of 2000 Iowa residents suggested that while gambling behaviour was relatively common, the relationship of such behaviour to perceived loss of control or the experience of negative consequences was quite moderate, indicating that gambling need not be associated with undesirable outcomes or feelings.…”
mentioning
confidence: 99%
“…Welte, Barnes, Tidwell, and Hoffman (2011) find evidence of this trend. Hraba et al (1990) uncover a negative correlation between age and gambling, while Humphreys, Lee, and Soebbing (2010) report a positive impact of age on gambling expenditures. As per Feeney and Maki (1997), individuals over 70 years of age are almost three times as likely to be non-gamblers compared to those between the ages of 18 and 34.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Men tend to seek excitement and financial gain when they gamble, while women do so to escape boredom and loneliness (Trevorrow & Moore, 1998). Hraba et al (1990) and Humphreys et al (2010) both report a positive effect of being male on gambling expenditure. The effect of residential area on gambling participation is less obvious.…”
Section: International Gambling Studies 97mentioning
confidence: 99%
See 2 more Smart Citations